Seed value chain development in the Global South: Key issues and new directions for public breeding programs - Donovan, Jason; Rutsaert, Pieter; Spielman, David J.; Shikuku, Kelvin Mashisia; Demont, Matty (SAGE Publications, 2021)
Where CGIAR breeding programs rely on the private sector for the multiplication and distribution of improved cultivars, persistent challenges have dampened their impact on varietal adoption and turnover rates. Part of the problem is that research and practice in CGIAR and among its national breeding program partners tend to treat the private sector as a vehicle for seed delivery, rather than as commercial businesses facing a range of unique constraints and threats. This paper adopts a value chain framework to examine these relationships and pathways for improved varietal adoption/turnover outcomes in three cases: hybrid maize, farmed fish, and rice. In the first two cases, weak incentives and high risks left seed companies reluctant to invest in the marketing and quality assurance efforts needed to realize near-term impacts at scale from breeding investments. In the third case, seed companies played an insignificant role: grain traders supplied certified seed to smallholders, potentially prioritizing consumers’ quality preferences over climate-resilience and stress-tolerance traits for farmers. The findings raise important questions about the role of CGIAR and national breeding programs; specifically, how these programs can effectively support the private sector to deliver impact at greater scale, how consumer preferences are captured in trait prioritization within breeding programs, and what types of incentive mechanisms can be changed within breeding programs to advance a genuine shift towards ‘demand-oriented’ plant breeding.